Intuitionism in Mathematics Education: A Bibliometric Analysis of Major Trends and Future Directions Over the Past Decade - Abdul Rahman; Khadijah, Khadijah; AM. Hindi, Alfiah Nurfadhilah (International Journal of Education, Vocational and Social Science, 2026)
Mathematical intuition is widely acknowledged as a fundamental component of mathematical thinking, influencing conceptual understanding, reasoning, and learning processes. However, research on mathematical intuition in mathematics education has evolved across multiple disciplines and publication venues, resulting in a fragmented and heterogeneous body of literature. This study aims to systematically map research trends, thematic structures, and future research directions in the field through a bibliometric analysis of Scopus-indexed publications published between 2005 and 2025. Employing a descriptive-quantitative bibliometric approach, publication metadata were analyzed using the bibliometrics package in R and VOS-viewer, focusing on publication trends, document types, geographical distribution, international collaboration networks, keyword co-occurrence, and thematic evolution. The findings reveal a clear shift from early philosophical and epistemological inquiries, such as intuitionism, truth, and justification, toward more pedagogical, cognitive, and practice-oriented research themes, including mathematics education, diagrammatic reasoning, embodied cognition, and mathematical knowledge. Despite the global growth of publications, international research collaboration remains limited and unevenly distributed across regions. Thematic evolution analysis indicates that mathematical intuition consistently occupies a central position, functioning as a conceptual bridge between foundational philosophical perspectives and contemporary instructional concerns. Based on these findings, this study recommends several priority directions for future research, including research on visual, diagrammatic, and embodied approaches to fostering intuition.